The ultrastructure changes of Haemonchus contortus exposed to bamboo leaves (Gigantochloa apus) aqueous extract under in vitro condition - Budi Purwo Widiarso; WISNU NURCAHYO; KURNIASIH KURNIASIH; JOKO PRASTOWO (Society for Indonesian Biodiversity, 2021)
Abstract. Widiarso, Nurcahyo W, Kurniasih, Prastowo J. 2021. The ultrastructure changes of Haemonchus contortus exposed to bamboo leaves (Gigantochloa apus) aqueous extract under in vitro condition. Biodiversitas 22: 1-5. The ultrastructural changes induced in adult Haemonchus contortus in vitro using the aqueous extract of bamboo leaves were assessed using scanning electron microscopy (SEM). The H. contortus adult females were obtained from three groups and treatment was repeated thrice. The first group (T0) was not treated with bamboo leaves; 100% of the worms lived. The second group (T1), treated with 0.1% bamboo leaf-extract, had 50% mortality 4 h after examination. The third group (T2), treated with 1% bamboo leaf-extract, had 100% mortality 4 h after examination. Five worms used per treatment were submerged in ethanol and incubated for 24 hours. The ultrastructural changes observed by SEM revealed structural alteration of the worm surface after in vitro contact with the bamboo leaf aqueous extract and compared to the control worms. The main changes concerned the anterior end or cephalic region, cuticle surface, and vulva flap area. The structural modification of the external part of the female reproductive system was found only in vitro. The structural changes found in the worms exposed to the bamboo leaves might affect their motility and nutrition with possible consequences on their reproduction. Transmission electron microscopy may help to understand the external changes observed in H. contortus.